Field test and reporting of disaster waste mapping in flood-affected areas of Kodagu district - B C Narasimha; Ramachandra Kamath; Sharvanan Eshwar Udayar; Ashwini Madeshan (Wolters Kluwer Medknow Publications, 2022)
Introduction: Floods are the most commonly occurring hydrological disasters in India. The disaster wastes (DWs) produced in floods involve various departments to clear the waste and consume more resources. Thus, the study was conducted to assess the type and visual quantity of DW during the initial recovery phase in flood-affected areas of the Kodagu district. Materials and Methods: A qualitative study was conducted in randomly selected 10 flood-affected areas in September 2019. Data were collected by a structured questionnaire and analyzed using Epi Info version 7.2. Results: The DWs were present in all 10 areas and it was classified into seven types. Out of 10 flood-affected areas, the majority of the areas had packaging wastes (nine areas) and bedding/furniture/cloth/textile waste (nine areas), followed by rubble/building material (six areas), electrical/electronic waste (five areas), food waste (three areas), and toxic/harmful/hazardous waste and biomedical waste/hospital waste (two areas). The total DW visual quantity was 6220 kg and was highest for rubble/building material DW. Conclusions: The DWs were containing both biomedical and nonbiomedical wastes. The wastes clogged the canals and polluted mainly water and soil. The visual quantity of DW was more and clearing the waste was difficult without the vehicles.